The Involvement of Noradrenaline in Rapid Eye Movement Sleep Mentation - Gottesmann, Claude (Frontiers in Neurology, 2011)
Noradrenaline, one of the main brain monoamines, has powerful central influences on forebrain neurobiological processes which support the mental activities occurring during the sleep–waking cycle. Noradrenergic neurons are activated during waking, decrease their firing rate during slow wave sleep, and become silent during rapid eye movement (REM) sleep. Although a low level of noradrenaline is still maintained during REM sleep because of diffuse extrasynaptic release without rapid withdrawal, the decrease observed during REM sleep contributes to the mentation disturbances that occur during dreaming, which principally resemble symptoms of schizophrenia but seemingly also of attention deficit hyperactivity disorder.